1980
DOI: 10.1128/aac.17.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subminimal inhibitory concentrations of Erythromycin, Clindamycin, and Pristinamycin on the penicillinase production of Staphlyococcus aureus

Abstract: The influence of subminimal inhibitory concentrations of erythromycin, clindamycin, and pristinamycin on the penicillinase production of Staphylococcus aureus was tested in 12 strains. Of the 36 experiments performed, 16 (44%) showed a lack of influence, 10 (28%) displayed an increase, and 10 revealed a decrease in penicillinase activity. The maximal effect produced was generally induced by concentrations ranging from ¼/ to 1/32 the minimal inhibitory concentration, irrespective of the susceptibility of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…This synergy was due to the inhibition of A-lactamase synthesis by chloramphenicol and has been shown to be operative both in vitro and in vivo (15,18). In similar studies with Staphylococcus aureus, Michel et al demonstrated that clindamycin diminished penicillinase production by this organism (16). This effect, however, occurred only in tests with clindamycin-susceptible strains.…”
Section: Downloaded Frommentioning
confidence: 86%
See 1 more Smart Citation
“…This synergy was due to the inhibition of A-lactamase synthesis by chloramphenicol and has been shown to be operative both in vitro and in vivo (15,18). In similar studies with Staphylococcus aureus, Michel et al demonstrated that clindamycin diminished penicillinase production by this organism (16). This effect, however, occurred only in tests with clindamycin-susceptible strains.…”
Section: Downloaded Frommentioning
confidence: 86%
“…This derepression may occur via oneof two mechanisms: (i) spontaneous mutation of the wild type to a stably derepresaed -state or (ii) reversible derepression of the wild type by a 1-lactamase inducer (9,10,12,19). The former mechanism has been shown to be responsible for the, emergence of multiple ,B-lactam resistance during therapy with new cephalosporins (3,17,20),> whereas the latter mechanism has been shown to be responsible for the antagonism of 1-lactai drugs by cefo,.itin (8,, 11, '2, 27 First, it has been shown to inhibit synthesis of certain proteins in gram-positive bacteria without affecting others (5,6,16,23 possessing cefoxitin-inducible P-lactamases (10,17,20,22). The stable derepressed mutant of Enterobacter cloacae 55 was selected in the laboratory and has been described in detail previously (10 24,1983 suspended in broth (10' CFU/ml) containing the antibiotics and incubated at 37°C in air for 24 h. At various time points, samples were removed and the number of viable CFU per milliliter was determined by agar dilution plate counts performed in duplicate.…”
mentioning
confidence: 99%
“…have been shown to be derepressed by clindamycin (a lincomycin derivative) (29). It also inhibits penicillinase production by clindamycinsusceptible strains of Staphylococcus aureus (23). Effects of these antibiotics on P-lactamase synthesis seem to differ among types of 1-lactamases and bacterial strains.…”
Section: Results Inmentioning
confidence: 99%
“…In a recent study on the influence of sub-MICs of erythromycin, clindamy cin and pristinamycin on the penicillinase production of S. aureus [9], we found an increase in the penicillinase activity in 28% and a decrease in 28% of the experi ments. These effects were irrespective of the susceptibility of the strain to the drug.…”
mentioning
confidence: 99%
“…Of the 36 experiments performed, 16 (44%) dis played an increase and 9 (25%) produced a decrease in the penicillinase activity of the strains. These effects were observed at concentrations ranging from 1:2 to 1:2,048 of the respective minimal inhibitory concentration, irrespective of the susceptibility of the strain to the aminoglycoside drug.Effects of subminimal inhibitory con centrations (sub-MIC) of antibacterial drugs on various bacterial enzymatic sys tems have been reported [I,[4][5][6][7][8][9] II], In a previous report, we have shown that the sub-MIC of chloramphenicol can inhibit beta-lactamase production in gram-nega tive bacilli [7] and in Staphylococcus au reus [8], and that this inhibition sometimes leads to a synergistic bactericidal effect in vitro [7,8] …”
mentioning
confidence: 99%